Respuestas
Respuesta dada por:
0
x/7 = (x + 3)/3
3x = 7x + 7 * 3
3x = 7x + 21
3x - 7x = 21
- 4x = 21
x = 21/-4
Solución :
x = - 21/4
3x = 7x + 7 * 3
3x = 7x + 21
3x - 7x = 21
- 4x = 21
x = 21/-4
Solución :
x = - 21/4
Respuesta dada por:
0
x/7 = (x + 3)/3
3x = 7x + 7 * 3
3x = 7x + 21
3x - 7x = 21
- 4x = 21
x = 21/-4
Solución :
x = - 21/4
3x = 7x + 7 * 3
3x = 7x + 21
3x - 7x = 21
- 4x = 21
x = 21/-4
Solución :
x = - 21/4
Preguntas similares
hace 7 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años